Constru????o de um ??ndice de dividendos para an??lise de bolhas racionais no mercado de a????es brasileiro - Ribeiro, Jussara (2016)
The existence of bubbles in stock markets can be detected by analyzing the relationship between stock prices and dividends. In Brazil, several studies use the Bovespa index as a proxy for stock prices, but differ in the index used as a proxy for dividends paid in the country. There are studies that create a monthly dividend index based on the theoretical portfolio and on the methodology of the Bovespa index. However, this dividend index has periods of great instability due to high concentration in the participation of some shares in the index. The objective of this study was to create an index that represents the dividend distribution in the Brazilian stock market using series provided by the Central Bank and the IBGE. The dividend index showed a smoother behavior, without periods of great instability or breaks. It was used as a proxy of the dividends in tests to verify the presence of bubbles. Three types of rational bubbles were studied: explosive bubbles, periodically collapsing bubbles and intrinsic bubbles. The tests results indicated that it is not possible to rule out the presence of explosive bubbles and detected evidences of the presence of periodically collapsing bubbles in the Brazilian stock market in this period. However, no evidence of the presence of intrinsic bubbles was found.